Analisis Semiotika Ekspresi Wajah dalam Sitkom Friends Episode “The One with the Girl Who Hits Joey” Berdasarkan FACS Paul Ekman - Mutia Poppy Berliani; Sholihatin Nasihah; Rifa’ Syahidah (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to analyse the communication signs contained in the series Friends Season 5, Episode 15 entitled ‘Girl Who Hits Joey’ using semiotic analysis of Paul Ekman's Facial Action Coding System (FACS). This research uses descriptive qualitative method. The research data was obtained from the fifth season of the television sitcom America Friends aired on NBC from 24 September 1998 to 20 May 1999. Data collection techniques were reading, observation (watching) and note taking. Data analysis was done by data reduction, data presentation, and conclusion drawing. The results showed that in the television sitcom America Friends there is an explanation of the signs and meanings of expressions that are transparent in the continuity of the running of the communication represented through verbal and nonverbal signs. The values are expressed explicitly through conversations and monologues of the characters, and expressed implicitly through the actions and attitudes of the characters in living life. Thus, it can be concluded that through the medium of television sitcoms, Actors are able to convey these values and ensure that every emotion felt by their characters is perfectly expressed on their faces.